2021
DOI: 10.3389/fmars.2021.735011
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Inter-Annual Variability of the Freshened Surface Layer in the Laptev and East-Siberian Seas During Ice-Free Periods

Abstract: This work is focused on the structure and inter-annual variability of the freshened surface layer (FSL) in the Laptev and East-Siberian seas during ice-free periods. This layer is formed mainly by deltaic rivers among which the Lena River contributes about two thirds of the inflowing freshwater volume. Based on in situ measurements, we show that the area of this FSL during certain years is much greater than the area of FSL in the neighboring Kara Sea, while the total annual freshwater discharge to the Laptev a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 80 publications
8
45
1
Order By: Relevance
“…To the extent of our knowledge, this paper provides the first thorough description of structure and variability of the Pechora plume. This work continues our previous studies of large river plumes in the Eurasian Arctic including the Ob-Yenisei plume in the Kara Sea (Osadchiev et al, 2017;Osadchiev et al, 2019;Osadchiev et al, 2021a;Osadchiev et al, 2021c), the Khatanga, Lena, Indigirka and Kolyma plumes in the Laptev and East-Siberian seas (Osadchiev et al, 2020b;Osadchiev et al, 2020c;Spivak et al, 2021;Osadchiev et al, 2021b), the large-scale freshwater transport in the Eastern Arctic (Osadchiev et al, 2020a;Osadchiev, 2021). Note that in this paper, we describe the response of a medium-size river plume (with area ~10 000 km 2 ) to external forcing, while our previous studies of the Arctic River plumes were focused on large river plumes (with area ~100 000 km 2 ).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…To the extent of our knowledge, this paper provides the first thorough description of structure and variability of the Pechora plume. This work continues our previous studies of large river plumes in the Eurasian Arctic including the Ob-Yenisei plume in the Kara Sea (Osadchiev et al, 2017;Osadchiev et al, 2019;Osadchiev et al, 2021a;Osadchiev et al, 2021c), the Khatanga, Lena, Indigirka and Kolyma plumes in the Laptev and East-Siberian seas (Osadchiev et al, 2020b;Osadchiev et al, 2020c;Spivak et al, 2021;Osadchiev et al, 2021b), the large-scale freshwater transport in the Eastern Arctic (Osadchiev et al, 2020a;Osadchiev, 2021). Note that in this paper, we describe the response of a medium-size river plume (with area ~10 000 km 2 ) to external forcing, while our previous studies of the Arctic River plumes were focused on large river plumes (with area ~100 000 km 2 ).…”
Section: Introductionsupporting
confidence: 88%
“…The vertical structure of the Pechora River plume was investigated using in situ data obtained during the surveys of RV Kartesh and Dalnie Zelentsy in July-August 1993-1995, 2017-2021. The isohaline of 25 is regarded as the outer boundary of the Pechora plume, similarly to other large river plumes in the Arctic Ocean (e.g., Ob-Yenisei, Lena, Khatanga) (Osadchiev et al, 2020a;Osadchiev et al, 2021a;Osadchiev et al, 2021b). In case of the Pechora plume, in situ measurements demonstrate that both horizontal and vertical salinity gradients are observed at the isohalines of 23-27 (Figures 5, 6).…”
Section: Vertical Structure Of the Pechora Plumementioning
confidence: 99%
“…However, these river plumes affect a number of key physical, biological and geochemical processes (water balance, stratification, nutrient cycle, carbon cycle, acidification, etc.) across large marine areas including the Bay of Bengal [28,56,57], the South China Sea [58], the central Atlantic [59,60], and the Arctic Ocean [8,9,[35][36][37][61][62][63]. Moreover, spreading and mixing of Ob-Yenisei and Lena plumes in the Arctic Ocean determine the sea stratification in the area of seasonal sea ice formation, thereby affecting ice formation in the Arctic Ocean, seasonal variability in the Earth's albedo and planetary climate [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed significant seasonal variability of both characteristics of the Ob-Yenisei plume during ice-free season [8,35]. In June-July, during the peak river discharge, the Ob-Yenisei plume is low-saline (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and relatively shallow (10 m). Then, in August-October salinity of the plume steadily increases to 15-25, its depth also increases to 10-15 m. Total freshwater volume contained in the Ob-Yenisei plume accumulates during the ice-free season from ~600 km 3 in June-July to ~900 km 3 in October.…”
Section: Vertical Salinity Structure and Adtmentioning
confidence: 97%
See 1 more Smart Citation